2014
DOI: 10.4028/www.scientific.net/msf.794-796.939
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Situ</i> Isothermal Calorimetric Measurement of Precipitation Behaviour in Al-Mg-Si Alloys

Abstract: Isothermal time-temperature-precipitation (TTP) diagrams deliver important material data like temperature and time ranges critical for precipitation. During the last years an in-situ calorimetric method to record continuous cooling precipitation diagrams has been developed to application level by our group. However, isothermal TTP-diagrams were still determined by ex-situ analyses only. In this work in-situ measurements of precipitation reactions were carried out during isothermal soaking. Therefore the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For example, the relative volume fraction of the precipitates can be simply calculated by its initial, real-time, and final resistivity values (ρ 0 , ρ t , ρ f ) through the expression: f r = (ρ 0 − ρ t )/(ρ 0 − ρ f ) [29,31]. It is similar to those using the data obtained by DSC and isothermal calorimetry experiments [19,20]. Moreover, it is suggested that this method would be also useful for analysis of the cluster and GP zones evolution, since the variation of resistivity is highly related to them [24].…”
Section: Accuracy and Application Of The In-situ Resistivity Measurinmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, the relative volume fraction of the precipitates can be simply calculated by its initial, real-time, and final resistivity values (ρ 0 , ρ t , ρ f ) through the expression: f r = (ρ 0 − ρ t )/(ρ 0 − ρ f ) [29,31]. It is similar to those using the data obtained by DSC and isothermal calorimetry experiments [19,20]. Moreover, it is suggested that this method would be also useful for analysis of the cluster and GP zones evolution, since the variation of resistivity is highly related to them [24].…”
Section: Accuracy and Application Of The In-situ Resistivity Measurinmentioning
confidence: 87%
“…Significant achievements in the characterization of the precipitation behavior of AlMgSi alloys have been reached since the end of last centenary, with the assistance of advancing technologies, like High Resolution Transmission Electron Microscopy (HRTEM) [5][6][7][10][11][12][13], Atom Probe Tomography (APT) [1,[13][14][15][16][17], Differential Scanning Calorimetry (DSC) [18][19][20], electrical resistivity measurements [21][22][23][24][25][26], Phase Field Crystal (PFC) modeling [4,24], etc. The precipitation sequence has been established and gradually accepted as: supersaturated solid solution (SSSS)→clusters/GP…”
Section: Introductionmentioning
confidence: 99%
“…This cooling rate should be as high as possible in order to achieve the maximum supersaturation of Si and Mg in solid solution [24,[30][31][32]. The most sensitive temperature range at industrial cooling rates seems to be between 450 and 250 • C [24,31,33]. Prolonged solubilization treatments are necessary in order to ensure the total dissolution of the Mg 2 Si formed in the cooling after chemical homogenization.…”
Section: Introductionmentioning
confidence: 99%